Antioxidant Properties of Nitric Oxide in Cellular Physiological and Pathophysiological Mechanisms. The Implications of Biological Balance between NO and Oxidative Stress - Ridnour, Lisa A.; Thomas, Douglas D.; Mancardi, Daniele; Donzelli, Sonia; Paolocci, Nazerrano; Pagliaro, Pasquale; Miranda, Katrina M.; Krishna, Murali; Fukuto, John; Grisham, Matthew B.; Mitchell, James B.; Espey, Michael G.; et al. (Current Medicinal Chemistry - Anti-Inflammatory & Anti-Allergy Agents, 2004)
The function of nitric oxide ( NO) in pathophysiology remains confounding as both protective and cytotoxic effects of NO have been demonstrated in many disease processes. Nitric oxide chemistry culminating in the generation of oxidative as well as nitrosative intermediates have generally been proposed as mediators of pathophysiology and have overshadowed the antioxidant capabilities of NO. However, the counteracting role of NO in providing a balance under conditions of oxidative and nitrosative stress has been underappreciated. The purpose of this review is the discussion of the role of NO as an antioxidant and interceptor of more potent reactive intermediates in normal physiology and disease.
Keywords: Antioxidant